Application of CuFe2O4 For Photocatalytic Fenton Treatment of Glycerol Solution - Kong, Zi Ying; Cheng, C. K.; Khan, Maksudur R. (2015)
This study reports on the glycerol decomposition using photocatalytic fenton technique. Visible light-responsive CuFe204 photocatalyst was synthesized using sol-gel method employing Cu:Fe ratio of 1 :2 by mo!. In the presence of xenon lamp (250 W), the performance of photocatalytic fenton degradation of different concentrations of glycerol aqueous solution (27.36, 41.05, 54.73 and 68.41 mM), different concentrations of hydrogen peroxide (163.9, 327.8, 491.7, 655.6 and 819.5 mM) and different photocatalyst loadings (0.1, 1.0, 2.0 and 5.0 g/L) were studied. The results obtained show that a minimal amount of photocatalyst loadings (0.1 g/L) was needed to initiate the photocatalytic fenton reaction. When the concentration of glycerol was increased, the degradation of glycerol diminished; however increasing the concentration of H202 has increased the glycerol degradation. The degradation for initial glycerol concentration of 27.36 mM was 60.0% while at 67.41 mM glycerol concentration, the degradation attained 27.0%. Besides that, adding 819.5 mM H102 showed 30% degradation while adding 163.9 mM H202 only showed 5% degradation. Full factorial analysis was introduced to screen the factors in the photocatalytic fenton degradation of glycerol. The screening exercise indicates that the best conditions were 27.41 mM glycerol concentration, 819.5 mM H202 concentration and 5.0g/L photocatalyst load in gs in the experiment of four hours.